WORKSHOP AUDIO RECORDING SYSTEM PADA SEKAWAN TRAINING CENTER - Akbar Juliansyah; Gargazi Gargazi; Wirawan Putrayadi; Edi Haryanto (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
Data, Voice / Voice and Video are basic needs for information for people in the digital era. This is based on the trend of triple play technology, which is a technology trend that accommodates three services that are presented in a customer service. The development of meeting the basic needs of the digital community cannot be separated from the development of the infrastructure that can be passed. This should be the basis for understanding the digital community that, in meeting the basic need for information, there is always a new technique being born. And the birth of this new technology can change a paradigm and even be disruptive. Voice as a need for digital society cannot be separated from the use of communication technology. Communication that is shared by users who interact with each other, that is, interact and communicate with each other. Sekawan Trining Center is an institution that is very interested in the use of techniques in supporting organizational operations wherever they are located. Although the technique is developing rapidly, this is also accompanied by an increase in the costs that must be incurred in its implementation. For this reason, the utilization of existing techniques can be maximized to reduce costs that may arise. There are also technology platforms that use analog communication media to enable systems that can be used to connect with technologies that can be used to access digital data. The solution that can be applied to overcome this is an Audio Recording System.